Pengaruh DER, ROA dan ROE Terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di BEI - Nadhifah; Nanu Hasanuh (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
The stock price is a value that proves how well the company is in carrying out the company operations, so it's not surprising that the stock price is one of the indicators seen and taken into consideration by investors when they want to invest. However, it is unavoidable that the stock prices will rise and fall in a company because it’s caused by several factors. Then this research purposes to look at whether there is a relation between Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE) to stock prices. A total of 5 manufacturing companies in the 2015-2020 period were selected as research samples, and the researcher choose purposive sampling as a form of a sampling method. The data analysis utilized is using classical assumption test and regression test. The results of the data that have been collected and then processed show that there is an influence that exists between the DER on the Stock Price, but the ROA and ROE don’t partially affect the Stock Price. Then simultaneously between the DER, ROA, and ROE, there is an effect on the Stock Price.